Rare Variants in Novel Candidate Genes Associated With Nonsyndromic Patent Ductus Arteriosus Identified With Whole-Exome Sequencing - Gao, Ying; Wu, Dan; Chen, Bo; Chen, Yinghui; Zhang, Qi; Zhao, Pengjun (Frontiers in Genetics, 2022)
Abstract Background: Patent ductus arteriosus (PDA) is one of the most common congenital heart defects causing pulmonary hypertension, infective endocarditis, and even death. The important role of genetics in determin-ing spontaneous ductal closure has been well-established. However, as many of the identified variants are rare, thorough identification of the associated genetic factors is necessary to further explore the genetic eti-ology of PDA. Methods: We performed whole-exome sequencing (WES) on 39 unrelated nonsyndromic PDA patients and 100 healthy controls. Rare variants and novel genes were identified through bioinformatic filtering strategies. The expression patterns of candidate genes were explored in human embryo heart samples. Results: Eighteen rare damaging variants of six novel PDA-associated genes (SOX8, NES, CDH2, ANK3, EIF4G1, and HIPK1) were newly identified, which were highly expressed in human embryo hearts. Conclusions: WES is an efficient diagnostic tool for exploring the genetic pathogenesis of PDA. These findings contribute new insights into the molecular basis of PDA and may inform further studies on genetic risk factors for congenital heart defects.